O sertão também é punk: a trajetória do movimento punk em Delmiro Gouveia (alto sertão alagoano - 1984 a 1996) - Lima, José Rinaldo Queiroz de (2020)
This master's dissertation aims to debate the history of the punk movement in Delmiro Gouveia, high backcountry in Alagoas state, taking the years 1984-1996 as a timeline. The northeastern hinterland is approached as a diversified space in political, social, cultural and geographical terms, with characteristics that influence the formation of social resistance movements, such as the punk movement. Thus, we seek to understand through the historiographical debate, the context and the temporalities in which the movement was formed in the city, observing the social and cultural experience of its participants, and also the movement's militancy after its formation. The debate carried out in this research starts from the analysis of written documentary sources, audiovisual and oral sources, the oralities being preponderant for the debate of history, reports that were crossed with each other and with the documentary sources, which were also confronted. The results obtained show the formation of the punk movement in Delmiro Gouveia, built by poor young people who identified with the aesthetics and ethics of the movement and saw it as the reinvention of forms of existence and resistance, engaging in political-social struggles, always questioning the powers established at local, national and international levels. We conclude that the movement, in Delmiro Gouveia, contributed socially, politically and culturally in terms of information, knowledge and politicization, promoting political and social debate and reflection in the city through socio-cultural manifestations.